Anti‐psoriatic effect of myeloid‐derived suppressor cells on imiquimod‐induced skin inflammation in mice. (15th January 2019) - Kim, Chang‐Hyun; Yoo, Jung Ki; Jeon, Seong Ho; Lim, Chi‐Yeon; Lee, Ju‐Hee; Koo, Deog‐Bon; Park, Mi‐Young
Abstract: Myeloid‐derived suppressor cells (MDSCs) play an important role in controlling the immune response against cancer and in suppression of autoimmunity and allergic inflammation. However, the beneficial effects of MDSCs on the experimental mouse model of psoriasis have not been reported. Therefore, we investigated the anti‐psoriatic effect of MDSCs on IMQ‐induced skin inflammation in mice and explored the mechanisms involved. Our results showed that administration of MDSCs (1 × 10 6 or 2 × 10 6 cells) suppressed the development of IMQ‐induced skin inflammation in mice as exemplified by a significant reduction in clinical severity scores and was associated with a reduction of histopathological changes, including inflammatory infiltration, epidermal hyperplasia and hyperkeratosis. The immunosuppressive effect of MDSCs (1 × 10 6 or 2 × 10 6 cells) corresponded to the production of Th1 cytokines (TNF‐α, IFN‐γ) and Th17 cytokines (IL‐17A and IL‐23) in the serum and dorsal skin. Administration of MDSCs (1 × 10 6 or 2 × 10 6 cells) also inhibited splenomegaly. Moreover, an increased percentage of CD4 + CD25 + FoxP3 + regulatory T (Treg) cells and decreased percentage of Th1 and Th17 cells were found in mice treated with MDSCs. Taken together, these results imply that MDSCs have immunomodulatory and immunosuppressive effects on disease progression in a murine model of psoriasis and that MDSCs could be used in preventive or therapeutic strategies for the management of autoimmune inflammatory skin disorders, such as psoriasis.